Mycological notes from the Tatra National Park. II - Wiesław Mułenko (Acta Mycologica, 2014)
The paper present a list of 141 species of parasitic fungi collected in the Tatra National Park in 1982-1992. Some fungi are new to the Polish mycoflora, or have been collected on new host plants or rare known from single localities only.